Treatment of acute myeloid leukemia in the next decade – Towards real-time functional testing and personalized medicine. Issue 6 (November 2017) - Lam, Stephen Sze-Yuen; He, Alex Bai-Liang; Leung, Anskar Yu-Hung
Abstract: Information arising from next generation sequencing of leukemia genome has shed important light on the heterogeneous and combinatorial driver events in acute myeloid leukemia (AML). It has also provided insight into its intricate signaling pathways operative in the disease pathogenesis. These have also become biomarkers and targets for therapeutic intervention. Emerging evidence from in vitro drug screening has demonstrated its potential value in predicting clinical drug responses in specific AML subtypes. However, the best culture conditions and readouts have yet to be standardized and the drugs included in these screening exercises frequently revised in view of the rapid emergence of new therapeutic agents in the oncology field. Testing of leukemia cell functions, including BCL2 profiling, has also been used to predict treatment response to conventional chemotherapy and hypomethylating agents as well as BCL2 antagonist in small patient cohorts. These platforms should be integrated into future clinical trials to develop personalized treatment of AML.